Safety : principles & practices in the laboratory - Ahmadun, Fakhru'l-Razi; Chuan, Teong Guan; Ismail, Mohd Halim Shah (Universiti Putra Malaysia Press, 2005)
Ignorance, carelessness or improper practices in the laboratory or the improper handling of hazardous or toxic materials may lead to work accidents and work-related ill-health. Laboratory users and administrators cannot afford to overlook these possible consequences due to the misconduct of laboratory practices and should decide how best to manage the health and safety aspects in the laboratory. This book has been written for safety representatives of colleges and universities, for lecturers, teachers and students., and for researchers working in laboratories. It is also for everyone responsible for laboratory safety, laboratory accidents and their consequences. The emphasis is on hazards to health and safety, with the focus on the general hazards in the laboratory, how they arise and how to prevent, how to eliminate and control them. Special hazards will also be discussed such as radiation hazards and human factors. This book also provides information on governmental and non-governmental agencies and authorities, emergencies contact numbers of relevant authorities, a list of Malaysia's occupational safety & health related legislation and some useful occupational safety & health websites. readers will find that the information contained in this book will serve as the foundation for laboratory users safety policy. A set of Laboratory Safety Forms for a typical laboratory is also available in the appendix for reference. Laboratory users can use and adapt these forms for their own laboratory requirements.